2011
DOI: 10.1515/jpem.2011.183
|View full text |Cite
|
Sign up to set email alerts
|

Stanozolol regulates proliferation of growth plate chondrocytes via activation of ERα in GnRHa-treated adolescent rats

Abstract: Improving the fi nal adult height is one of the most important aims for treatment of central precocious puberty. Stanozolol (ST) is a synthetic derivative of androgen. In this study, we investigated the effects and the mechanisms of ST on the proliferation of growth plate chondrocytes isolated from adolescent rats treated with gonadotropin-releasing hormone analogue (GnRHa). Treatment with ST resulted in time-and concentration-dependent effects on proliferation as determined by MTT and proliferating cell nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
(26 reference statements)
1
8
0
Order By: Relevance
“…Its properties include anabolic and/or androgenic activity [9], probably associated with its affinity for androgenic and, at lower doses, glucocorticoid receptors [10]. It has been demonstrated that stanozolol induces in vitro upregulation of osteoblast proliferation, collagen synthesis through transforming growth factor-b1 activity [11], chondrocyte secretion of insulin-like growth factor-1 [12], and, in rats, growth plate chondrocyte proliferation [13]. Moreover, it reduces NO production [12].…”
Section: Introductionmentioning
confidence: 99%
“…Its properties include anabolic and/or androgenic activity [9], probably associated with its affinity for androgenic and, at lower doses, glucocorticoid receptors [10]. It has been demonstrated that stanozolol induces in vitro upregulation of osteoblast proliferation, collagen synthesis through transforming growth factor-b1 activity [11], chondrocyte secretion of insulin-like growth factor-1 [12], and, in rats, growth plate chondrocyte proliferation [13]. Moreover, it reduces NO production [12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reveal that it stimulates a height velocity increase without bone age progression in patients with Turner syndrome undergoing oxandrolone treatment (19). Our previous study also showed that ST promotes the proliferation of growth plate chondrocytes (15). Therefore, we speculated that ST stimulates growth plate development through the promotion of chondrogenic differentiation in patients who were experiencing an inhibitory effect of GnRHa.…”
Section: Discussionmentioning
confidence: 85%
“…Rats were euthanized at 7 weeks of age. Hind limb specimens were dissected and fixed in 4% paraformaldehyde for histological analyses (n = 5 animals per group) ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations